(untitled) - Yuan, Fei (New York, 2007)
This book deals with the analysis and design of CMOS current-mode circuits for data communications. CMOS current-mode sampled-data networks, i.e. switched-current circuits, are excluded. Major subjects covered in the book include: voltage-mode and current-mode circuits – a critical comparison, the building blocks of current-mode circuits, design techniques for CMOS current-mode circuits, modeling of wire channels, electrical signaling for Gbps data communications, current-mode transmitters, current-mode receivers, delay-locked and phase-locked loops, switching noise and grounding of mixed-mode circuits, and ESD Protection for current-mode circuits.
Keywords: Metal oxide semiconductors, Complementary,Integrated circuits,Vi mạch bán dẫn, bổ sung,Mạch tích hợp